Vaccination of healthcare workers: is mandatory vaccination needed? - Helena C. Maltezou; Kalliopi Theodoridou; Caterina Ledda; Venerando Rapisarda; Maria Theodoridou (Expert Review of Vaccines, 2019)
Introduction: Vaccinations of healthcare workers (HCWs) aim to directly protect them from occupational acquisition of vaccine-preventable diseases (VPDs) and to indirectly protect their patients and the essential healthcare infrastructure. However, outbreaks due to VPDs continue to challenge healthcare facilities and HCWs are frequently traced as sources of VPDs to vulnerable patients. In addition, HCWs were disproportionately affected during the current measles outbreak in Europe. Areas covered: We reviewed the recent published information about HCWs vaccinations with a focus on mandatory vaccination policies. Expert commentary: Although many countries have vaccination programs specifically for HCWs, their vaccination coverage remains suboptimal and a significant proportion of them remains susceptible to VPDs. The increasing vaccination hesitancy among HCWs is of concern, given their role as trusted sources of information about vaccines. Mandatory vaccinations for HCWs are implemented for specific VPDs in few countries. Mandatory influenza vaccination of HCWs was introduced in the United States a decade ago with excellent results. Mandatory vaccinations for VPDs that may cause significant morbidity and mortality should be considered. Issues of mistrust and misconceptions about vaccinations should also be addressed.